A Neutrosophic β-Generalized α-Closed and d-Ideal-Based Framework for Cross-Border Digital Marketing Optimization in Fashion E-Commerce - Nuo Chen (Neutrosophic Sets and Systems)
Cross-border digital marketing in the fashion industry involves high levels of uncertainty, especially when targeting international audiences with diverse behaviors, cultures, and market conditions. Traditional marketing models often fail to handle such uncertainty effectively, leading to poor decision-making and wasted resources. This paper introduces a new decision-making model that uses advanced mathematical tools from neutrosophic logic to deal with ambiguity, inconsistency, and partial information. Specifically, it combines two key components: β-generalized α-closed sets (used to assess market openness) and neutrosophic d-ideals (used to ensure consistency in marketing strategies). Together, these tools help marketers evaluate which international markets are most suitable for specific campaigns, even when data is incomplete or unclear. A new decision function, called the Neutrosophic βGα-d Marketing Function, is presented. It calculates how compatible a marketing strategy is with a specific market by considering truth, uncertainty, and resistance levels. Through detailed examples and a case study involving fashion marketing across three regions, the model shows its ability to reduce risk, improve targeting, and support smarter campaign planning. This approach offers a structured and transparent way to make better marketing decisions in complex global environments.